The Effectiveness of Land and Water Based Resistance Training on Shoulder Rotator Cuff Strength and Balance of Youth Swimmers - Batalha, Nuno (2020)
The continuous execution of swimming techniques, supported mainly by the upper limbs, may cause shoulder rotator muscle imbalances, which leads to injuries. The aim of this study was to evaluate and compare the effects of two training programs on strength, balance and endurance of shoulder rotator cuff muscles in youth swimmers. Twenty-five male swimmers were evaluated and randomly divided into two groups - the land group (n = 13), which conducted a conventional dry-land training program with elastic bands, and the water group (n = 12), which conducted a water resistance program. In both groups, the level of strength of the shoulder rotators was evaluated with an isokinetic dynamometer on two occasions (baseline and after 10 weeks) using two protocols: i) three repetitions at 60o/s; ii) twenty repetitions at 180o/s. The land group significantly increased the unilateral ratios compared to the water group. The land group also decreased the external rotator levels of muscular fatigue. The dry-land training program conducted proved to be more effective than the one conducted in the water, allowing to reduce the muscle imbalance and to decrease muscle fatigue.